A construção discursiva do Ethos no álbum “Convoque seu Buda”, de Criolo - Freitas, Ana Cherllany Cardoso de (2023)
This research intends to analyze the construction of the ethos of the album “Convoque seu Buda”, by Criolo. The choice for studying the artist's rap song is due to its relevance in contemporary Brazilian music since it composes songs that discuss the representations of urban space in its conflicts. Thus, the ten songs contained in the album, the layout of the tracks, and the album cover will be the corpus used for this analysis, which adopts the theoretical perspective of Discourse Analysis, mainly about the studies of Dominique Maingueneau (1995, 2002, 2006, 2008a, 2008b, 2015, 2020a, 2020b), of which the most recent studies on ethos will be highlighted (MAINGUENEAU, 2020b), whose notion of fitting and framing will become important, as well as its dimensions, which are categorical, experiential and ideological. Linked to such concepts, we also address investments in language code and scenography (MAINGUENEAU, 1995). These concepts will be analyzed in the wake of Costa's (2001) application to the literary- musical discourse. By verifying how the ethos of the songs on the album under study are developed, we realize that there is, in the experiential dimension, an oscillation between the sour and transcendental character; in the categorical dimension, between the discursive role of the preacher and the rapper; and, in the ideological dimension, the anti-consumerist, social determinist and disbelieving positions of social institutions. Such characteristics, which are closely correlated, also relate to the scenographies and the language code. Furthermore, through the analysis of each song, we noticed elements that suggest that the album's ethos is the artist's own ethos, whose coercions carry out the processes of fitting and framing the ethos. Thus, the relationship between social criticism and disbelief in institutions responsible for the well-being of individuals, which allows the emergence of an attachment to mystical forces, raises this ethos of the artist. This analysis corroborates the importance of Criolo in the Brazilian Popular Music scenario as it portrays contemporary Brazil in the literary-musical discourse and enables rich contributions to the understanding, ultimately, of how his utterances legitimize social practices and are legitimized by them.